Creating nanoporous graphene with swift heavy ions. (April 2017) - Vázquez, H.; Åhlgren, E.H.; Ochedowski, O.; Leino, A.A.; Mirzayev, R.; Kozubek, R.; Lebius, H.; Karlušic, M.; Jakšic, M.; Krasheninnikov, A.V.; Kotakoski, J.; Schleberger, M.; et al.
Abstract: We examine swift heavy ion-induced defect production in suspended single layer graphene using Raman spectroscopy and a two temperature molecular dynamics model that couples the ionic and electronic subsystems. We show that an increase in the electronic stopping power of the ion results in an increase in the size of the pore-type defects, with a defect formation threshold at 1.22–1.48 keV/layer. We also report calculations of the specific electronic heat capacity of graphene with different chemical potentials and discuss the electronic thermal conductivity of graphene at high electronic temperatures, suggesting a value in the range of 1 Wm −1 K −1 . These results indicate that swift heavy ions can create nanopores in graphene, and that their size can be tuned between 1 and 4 nm diameter by choosing a suitable stopping power. Graphical abstract: